The influence of technical violation revocations on parole efficacy: employing competing risks survival analyses to address methodological challenges - Ostermann, Michael (Journal of crime and justice, 2020)
Failures among the community supervision population are a major contributor to prison populations. Revocations of parole supervision due to technical parole violations (TPRs) often result in the incarceration of a parolee for violating the terms of their supervised release. This study employs several strategies for integrating TPRs into the construct of recidivism, a common outcome measure in correctional evaluations. TPRs are either ignored, combined with rearrest, or treated as a competing risk to rearrest. Each framework is employed to estimate survival rates among multi-year prison release cohorts in which parolee supervision is stratified by actuarial risk level. Results suggest that the way TPRs are integrated into evaluations of parolee recidivistic behavior patterns can influence the magnitude and nature of a study’s results. This is significant as costly policy decisions are often informed by evaluation research focusing on time to failure measures. Methodological and ideological remedies are proposed.